Wikipedia, Dbpedia and the Polish Art Market: Data Enrichment and Analysis of Concepts’ Frequency in the Descriptions of Paintings and Authors - Filipiak, Dominik; Filipowska, Agata (Studia Oeconomica Posnaniensia, 2017)
Wikilinks are internal hyperlinks on Wikipedia, a popular Internet encyclopaedia. A unique article identifi er is hidden behind so-called surface form, which is a grammatical match of a given term accordingly to the context in which it occurs. Therefore, a given term can have multiple surface forms. Due to this fact it is possible to discover concepts (entries on Wikipedia) automatically in artists’ and lots’ descriptions on the pages of auction houses by searching for surface forms. Combining these data with traditional quantitative methods of art market research, such as linear regression, it is possible to discover, inter alia, popular motives and explore their statistical signifi cance and their impact on hammer price.